2024
DOI: 10.3390/mi15030317
|View full text |Cite
|
Sign up to set email alerts
|

Development of Drug Efficacy Testing Platform for Glomerulonephritis

Eun-Jeong Kwon,
Yunyeong Choi,
Shin Young Kim
et al.

Abstract: We developed a 3D glomeruli tissue chip for glomerulonephritis (GN) testing, featuring a gravity-driven glomerular filtration barrier (GFB) with human podocytes and endothelial cells with a bidirectional flow in the bottom channel. Using puromycin-induced GN, we observed decreased cell viability, increased albumin permeability, and reduced WT1 and nephrin compared to the normal GFB. Tacrolimus restored cell viability, reduced albumin permeability, and increased WT1 expression. Using serum from five membranous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Thus, we focused on human immortalized CIHP-1 cells known to present a phenotype and function very similar to those of primary podocytes. Most importantly, they can be efficiently differentiated at a large scale without using laborious protocols, as we have previously shown [13]. Our data showed that characteristic podocyte morphology, including long spindle-like projections, fine processes, short rounded projections, and interdigitations between cells, could be observed on day 7 of differentiation.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Thus, we focused on human immortalized CIHP-1 cells known to present a phenotype and function very similar to those of primary podocytes. Most importantly, they can be efficiently differentiated at a large scale without using laborious protocols, as we have previously shown [13]. Our data showed that characteristic podocyte morphology, including long spindle-like projections, fine processes, short rounded projections, and interdigitations between cells, could be observed on day 7 of differentiation.…”
Section: Discussionsupporting
confidence: 74%
“…Recent advances in kidney-on-a-chip or renal microfluidic device technology have demonstrated great potential for kidney disease modeling and assessment of drug-induced kidney injury by recapitulating in vivo tissue characteristics. A glomerulus-on-a-chip research study reported that a unique culture environment mimicking the in vivo physiological environment can elicit more potential in cultured cells than a conventional static culture [9][10][11][12][13]. Thus, it is a promising tool as an alternative to animal experiments.…”
Section: Introductionmentioning
confidence: 99%